Identification, Characterization and Antifungal Activity Test of Chemical Compounds from Methanol Extract of Macroalgae Padina australis Against Dandruff Fungus Malassezia globosa - Violetta Djohansah; Riong Seulina Panjaitan; Zuraida Sagala (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Padina australis is a species of brown macroalgae with potential as a natural source of bioactive compounds, including antifungal agents. This study aimed to identify the functional groups present in the methanolic extract of Padina australis using Fourier Transform Infrared (FTIR) spectroscopy and to evaluate its antifungal activity against Malassezia globosa through the disk diffusion method. FTIR analysis revealed the presence of hydroxyl (3433.41 cm⁻¹), aliphatic C–H (2916.47 cm⁻¹), carbonyl (1735.99 and 1643.41 cm⁻¹), amine (1573.97 and 1242.20 cm⁻¹), C–O, and carboxylate (COO⁻) groups, indicating key secondary metabolites such as flavonoids, phenols, esters, amines, and polysaccharides. Antifungal testing showed that the extract at a concentration of 100 ppm produced the largest inhibition zone (16.58 ± 4.71 mm), while the minimum inhibitory concentration (MIC) was determined at 12.5 ppm with an inhibition zone diameter ≥12 mm. These findings suggest that Padina australis holds promising potential as a natural source for developing antifungal therapies against Malassezia globosa.